Exotic dairy breed turns into exhausted dairy breed when forced to reproduce, lactate and perform work at the same time: On-farm testing of multipurpose breed, experience from Holetta area. - Larsen, C.E.S.; Kumsa, T.; Tegegne, Azage (Ethiopian Society of Animal Production, 2004)
Farming systems based on ox-cultivation is a millennium old tradition in Ethiopia. However, this farming system with its in high demand for grazing land, has come under increased pressure during the last century. Means of intensifying the mixed crop and livestock farming systems, which is predominant in the highlands, has to be found if Ethiopia shall escape the downward spiral of overexploitation, soil erosion and famine. A possible way could be to increase the livestock biodiversity by substituting the local Zebu oxen with more appropriated breeds of cows both capable of performing work, reproduce and give milk. In 1988 FARO and ILRI sat up a joint venture research programme at Holetta Research Station to test this idea. F1 crosses of Boran x Simmental and Boran x Friesian were used in the experiment. On-station research conducted from 1988 - 1995 showed that using these breeds of crossbred dairy cows for both milk production and draught work was a feasible technology as long as the increased energy requirement was met by adequate feeding. On-farm research conducted from 1995 -1998 with only Boran x Frisian crosses included 50 farmers stratified in three different resource endowment groups showed that short-term uptake of the dairy-draught technology was low. During the trial only 10% of all trial land were tillage by crossbred cows and the use of crossbred cows for work halted completely shortly after the end of the trial. In terms of on-farm milk production the introduction of crossbred cows had a significant impact, increasing revenue from milk sale increased up to ten times, compared to the traditional system with only Zebu cows. Milk yields differed significantly among resource endowment groups with cows from rich farmers performing best followed by cows from medium and poor farmers, respectively. Days to first post partum oestrus and calving interval were similar for the groups, but tended to increase over time. The reasons for low uptake of draught part of the technology were numerous, the most important being: Unwillingness to use the cows for ploughing, inadequate feeding, no alternative investment opportunities, land scarcity not perceived as a prevailing problem in the area and the chosen research approach. The question also remains if heavy Boran x Friesian crosses is the right breed for small-scale farmers.